In Vitro Cell Density Determines the Sensitivity of Hepatocarcinoma Cells to Ascorbate - Fan, Hsiu-Lung; Liu, Shu-Ting; Chang, Yung-Lung; Chiu, Yi-Lin; Huang, Shih-Ming; Chen, Teng-Wei (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) is the primary histological subtype of liver cancer, and its incidence rates increase with age. Recently, systemic therapies, such as immune checkpoint inhibitors, monoclonal antibodies, and tyrosine kinase inhibitors (TKIs), have been more beneficial than conventional therapies for treating HCC. Nonetheless, the prognosis of late-stage HCC remains dismal because of its high recurrence rates, even with substantial advances in current therapeutic strategies. A new treatment, such as a combination of current systemic therapies, is urgently required. Therefore, we adopted a repurposing strategy and tried to combine ascorbates with TKIs, including lenvatinib and regorafenib, in HepG2 and Hep3B cells. We investigated the potential functional impact of pharmacological concentrations of ascorbate on the cell-cycle profiles, mitochondrial membrane potential, oxidative response, synergistic effects of lenvatinib or regorafenib, and differential responsiveness between HepG2 and Hep3B cells. Our data suggest that the relative level of cell density is an important determinant for ascorbate cytotoxicity in HCC. Furthermore, the data also revealed that the cytotoxic effect of pharmacological concentrations of ascorbate might not be mediated via our proposed elevation of ROS generation. Ascorbate might be involved in redox homeostasis to enhance the efficacy of TKIs in HepG2 and Hep3B cells. The synergistic effects of ascorbate with TKIs (lenvatinib and regorafenib) support their potential as an adjuvant for HCC targeted TKI therapy. This research provides a cheap and new combinatory therapy for HCC treatment.